HUKUM JUAL BELI ON-LINE DENGAN KODE SEBAGAI HARGA PERSPEKTIF YUSUF AL-QARADHAWI (Studi Kasus: On-line Shop @FAMAS.STUFF) - Sri Julianti (ISLAMIC BUSSINESS LAW REVIEW, 2019)
Adding the code behind the price is one way that almost all on-lineshop do. Adding the code behind the price is one way to make it easier for the on-lineshop admin when registering customers. The problem in this thesis, the authors found a fact about the field about one on-lineshop that requires customers to add a code behind the price when the customer makes payments via bank transfer. This thesis discusses how Yusuf Al-Qaradhawi's perspective on pricing contains fraud and elements of wrongdoing, as well as the proposition used by Yusuf Al-Qaradhawi and how the views of on-lineshop owners and customers in on-lineshop @FAMAS.STUFF related to adding code behind price. The research method used is qualitative research, which is meant by qualitative research is a research method that is based on the philosophy of postpositivism, which is used to examine the conditions of natural objects which later the results of qualitative research emphasize the meaning rather than generalization. In this study the authors also use research steps that can make research more systematic, accurate and have a good analysis of this study. Yusuf Al-Qaradhawi who forbids the sale and purchase which contains elements of fraud and elements of legal wrongdoing is haram. The reason given by Yusuf Al-Qaradhawi about the prohibition of buying and selling that contains these elements is so that no party is harmed because Islam justifies everything that is good.